Sejarah Nasional Indonesia - Sartono Kartodirjo (Balai Pustaka, 1977)
ws/Oen, Jil.1=c.1-3; Jil.2=c.1-2,jl.5.c.1; sn,jl.4,c.1/ir, jil.1,c.4 ; jil.6,c.1/ast, jil.6 =c.2, jil.4 =c.11/ast jil.1 =c.5/oen, Jil.5=c.2/ast, jil.2 =c.3/why, jld.2=c.4/tr, jil.6=c.3/en, jil.3-c.1/ad, jil.3.c.2/ast, jil2 =c.5